Halal training: issues and challenges from trainers’ perspectives in Halal Products Research Institute (HPRI) / Nur Hafizah Harun … [et al.] - Harun, Nur Hafizah; Abdullah, Muhamad Amir Nur Hakim; Mohd Ashmir Wong, Muhammad Syukri; Mamat, Norazlina; Moidin, Shofiyyah (Academy of Contemporary Islamic Studies (ACIS), 2021)
Halal education is an essential requirement to increase understanding and awareness among the community and industrial players about halal concepts. The development of the halal industry in Malaysia and on a global level has shown a lot of positive growth every year. Involvement from various agencies such as JAKIM, HDC, and private halal consultants and training centers have helped a lot in terms of education development and providing training modules as a guideline to conduct halal training. However, halal trainers often encounter some participants with different educational backgrounds while conducting halal training, which eventually affects the training delivery and the quality of the training itself. Therefore, the purpose of this research is to analyse the issues and challenges faced by the trainers during halal training. This study adopted a qualitative method where the data was obtained by an interview session with halal trainers from HPRI. Next, the data obtained were analysed using thematic analysis. The findings show that the issues and challenges faced by halal trainers can be categorised into several criteria and factors such as language barrier, misunderstanding, and participants’ educational background. This research aims to contribute to the development of halal training in halal education in the future.